Perinatal determinants of D-dimer levels in a cross-sectional study of low risk pregnant women. (June 2016) - Murphy, NM; Khashan, AS; Broadhurst, DI; Gilligan, O; O'Donoghue, K; Kenny, LC
Background: To examine perinatal determinants of the antenatal levels of D-dimers. Methods: Cross-sectional study of 760 low risk pregnant women recruited into five gestational groups. Variables examined in antenatal groups included maternal age, body mass index, parity, smoking, family history venous thromboembolism (VTE) and previous use of the oral contraceptive pill (OCP). Onset of labour and mode of delivery were also examined in the post-natal group. Results: D-dimer levels in group 4 (38–40 + 6) were significantly lower in the women with a history of taking the OCP when compared to those that had not taken it in the past ( P = 0.027). In the day 2 post-natal group, the median level of D-dimer was significantly higher in primparous when compared to multiparous women ( P = 0.015). The median D-dimer levels were significantly lower in the elective Caesarean section group in comparison to spontaneous onset ( P = 0.003) and induction of labour ( P = 0.016). When the mode of delivery was examined, the median D-dimer levels were significantly lower in those that had an elective Caesarean section when compared to normal vaginal delivery ( P = 0.008) and instrumental vaginal delivery ( P = 0.007). Women post elective Caesarean section had a significantly lower D-dimer than those after emergency Caesarean section ( P = 0.008). Discussion: There are some significant differences in D-dimer levels when certain perinatal determinants are examined. This work is potentially beneficial to the future diagnosis of VTE in pregnancy as it supports previously published recommended D-dimer levels for the diagnosis of VTE in pregnancy.